Biodiesel Characterization Study from Castor Oil (Jatropha Curcas L) with CaO/K2O Catalyst - Santoso, Aman; Sumari, Sumari; Asrori, Muhammad Roy; Januarti, Wenny (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
Biodiesel is still being developed as a renewable fuel to replace a diesel fuel. Biodiesel production of castor oil has high potential because the oil did not compete with foods. Furthermore, a transesterification process can be optimized by heterogeneous base catalysts. Thus, this study aims to: (1) synthesize CaO/K2O catalysts to be used in the transesterification process, (2) synthesize biodiesel of castor oil and characterize it according to SNI 7182:2015, and (3) study the effect of CaO/K2O variations on biodiesel product. This laboratory experimental research was carried out in the following stages: (1) characterization of castor oil, (2) esterification, (3) preparation of CaO/K2O catalyst, (4) transesterification, and (5) characterization of the synthesized methyl ester. The results showed that the characterization of castor oil included a density of 1.074 g/mL, an acid number of 9.5 mg/g, a free fatty acid (FFA) of 5.09%, and a viscosity of 701 cSt. Stratified esterification and transesterification showed a significant effect on reducing FFA, so the characterization of the transesterified methyl ester from the best catalyst variations (CaO/K2O 1:2) included a density of 1.016 g/mL, an acid number of 1.1 mg/g, FFA content of 0.58%, moisture content of 1.1%, viscosity 43.55 cSt, and refractive index (25) of 1.466.